PENGARUH DOSIS PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hypogea L.) DI DESA REROROJA KECAMATAN MAGEPANDA KABUPATEN SIKKA - Yoseph Siga; Yovita Yashinta Bolly (AGRICA, 2019)
Peanut belongs to the Leguminosae family, which has the opportunity to develop agro- industry in supporting efficient and effective regional economic development. The purpose of this study was to determine the effect of giving chicken manure to the growth and production of peanut plants as well as the optimal dose of chicken manure for the growth and production of peanut plants. The study conducted from June 2018 to October 2018. The study used a randomized block design (RBD) with six treatments and four replications so that twenty-four (24) trial units were obtained. Factor A0: No fertilizer (control), A1: 1.5 kg, A2: 3 kg, A3: 4,5, A4: 6, A5: 7 Kg per bed. The results showed that the provision of chicken manure significantly affected the height of plants aged 15 and 30 HST. Significantly affect the number of leaves of plants aged 15 and 30 HST. Very significant effect on the number of pods aged 90 Hst and very significant effect on the weight or wet weight of peanut pods aged 90 Hst. The dose of chicken manure 25 tons/ha in this study is the best fertilizer dosage treatment to provide the highest growth and production of Hypoma one peanut.